2017
DOI: 10.1097/rli.0000000000000352
|View full text |Cite
|
Sign up to set email alerts
|

Quantification and Assessment of the Chemical Form of Residual Gadolinium in the Brain After Repeated Administration of Gadolinium-Based Contrast Agents

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

35
213
1
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(252 citation statements)
references
References 49 publications
(74 reference statements)
35
213
1
3
Order By: Relevance
“…The increased signal intensity in the brain on MRI scans is not always reliable and comparable due to different field strengths (1.5 Tesla and 3.0 Tesla), and the use of different T1-weighted sequences or sequence parameters. Moreover, the proton T1 relaxivity also depends on the molecular weight of the molecule to which the Gd-ions or Gd-contrast media molecules are attached (either soluble macromolecules or insoluble cell components), the water residence time of the coordinated water molecules, and, for some GCCAs, the presence of albumin [15,16]. It is therefore unclear to what extent the increased signal intensity in the brain truly reflects higher gadolinium concentrations [17].…”
Section: Methodological Limitations Of Current Studiesmentioning
confidence: 99%
“…The increased signal intensity in the brain on MRI scans is not always reliable and comparable due to different field strengths (1.5 Tesla and 3.0 Tesla), and the use of different T1-weighted sequences or sequence parameters. Moreover, the proton T1 relaxivity also depends on the molecular weight of the molecule to which the Gd-ions or Gd-contrast media molecules are attached (either soluble macromolecules or insoluble cell components), the water residence time of the coordinated water molecules, and, for some GCCAs, the presence of albumin [15,16]. It is therefore unclear to what extent the increased signal intensity in the brain truly reflects higher gadolinium concentrations [17].…”
Section: Methodological Limitations Of Current Studiesmentioning
confidence: 99%
“…15 For all 3 linear agents evaluatedgadodiamide, gadopentetate dimeglumine, and gadobenate dimegluminethe residual Gd was present in at least 3 distinctive forms-soluble small molecules (likely the intact chelate), soluble macromolecules, and insoluble Gd, with no relevant differences between these agents. The authors hypothesized that the latter 2 forms were most likely responsible for the residual T1 high signal intensity seen in clinical patients in the dentate nucleus and other structures.…”
Section: Recent Animal Investigationsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] Stability both in in vitro and in vivo, relative to the release of gadolinium (which depends upon both thermodynamic and kinetic stability), has been shown to be markedly superior for the macrocyclic agents when compared with the linear agents. [14][15][16][17] The linear nonionic agents (specifically gadodiamide and gadoversetamide) are also markedly less stable by this measure than the linear ionic ones. 18 All GBCAs cause, in a small percent of patients, mild adverse reactions, including nausea and hives, with a large number of articles in the scientific literature debating the relative percent of such with the different agents.…”
mentioning
confidence: 99%
“…Furthermore, the Gd deposition has also been observed in the cerebellar cortex [3,7]. Gd compounds deposited in the cerebellum consist of both soluble and insoluble forms [1,2]. Soluble form may be intact GBCA, whereas insoluble form may be Gd bound with organic or inorganic anions, although the exact chemical nature of insoluble form has not yet fully clarified.…”
mentioning
confidence: 99%
“…Studies using animal models have shown that GBCAs may be deposited in the brain after repeated injections [1][2][3]. Tissue depositions of linear GBCAs are much higher than those of macrocyclic GBCA.…”
mentioning
confidence: 99%